Assessment of Biomass Energy Potentials and Appropriate Sites in Nigeria using GIS Computing Strategy - Ukoba, M.O.; Diemuodeke, E.O.; Briggs, T.A.; Okedu, K. E.; Owebor, K.; Imran, M.; Ojapah, M.M.; Agbinya, Johnson I. (Proceedings of International Conference for ICT (ICICT) - Zambia, 2023)
The geographical variability of biomass energy is an issue that requires the optima location of biomass energy facility. This paper presents a multicriteria GIS-based assessment of biomass energy potentials and appropriate siting of biomass plant in Nigeria. The study applies the weighted overlay multicriteria decision analysis method. Crop, and forest areas; settlement (energy supply areas); shrub/grass lands; barren land; waterbodies; distance from water sources; road accessibility; topography; and aspect are the criteria that were considered for locating the biomass facility in this study. The results suggest that the theoretical, technical and economical energy potentials of crop residues are highest in the north-east region of Nigeria and estimated at 1163.32, 399.73 and 110.56 PJ/yr, respectively, and least in the south-east at 52.36, 17.99 and 4.98 PJ/yr, respectively. The theoretical, technical and economical energy potentials of forest residues are highest in the north-west, estimated at 260.18,156.11 and 43.18 PJ/yr, respectively, and least in the south-east at 1.79, 1.08 and 0.30 PJ/yr, respectively. The GIS computing was able to identify the most suitable areas for siting biomass plants across Nigeria, in the Northern part of the country, and include; Niger, Zamfara, the Federal Capital Territory, Nassarawa, Kano, Kebbi, Kaduna and Borno state.